Development and Evaluation of a Nanoporous Iron (Hydr)oxide Electrode for Phosphate Sensing - Moss, Rachel E.; Jackowski, Jennifer J.; Castilho, Michelle de Souza [UNESP]; Anderson, Marc A. (Wiley-v C H Verlag Gmbh, 2011)
Nanoporous iron (hydr) oxide electrodes are evaluated as phosphate sensors using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The intensity of the reduction peak current (I-cp) of the ferrihydrite working electrode is tied to phosphate concentration at low pH; however, a hematite electrode combined with the use of EIS provided reliable sensing data at multiple pH values. Nanoporous hematite working electrodes produced an impedance phase component (theta) that shifts with increasing phosphate, and, at chosen frequencies, theta values were fitted for the range 1 nM to 0.1 mM phosphate at pH 4 and pH 7 in 5 mM NaClO4.
Keywords: Ion-selective electrodes; Iron (hydr)oxides; Nanoporous coatings; Phosphate sensor; Sol-gel methods